Improving the Technology for Training Personnel in the Service Sector - ZVYAGINTSEVA, Elena Petrovna; ZENKINA, Irina Vladimirovna; MANAKHOVA, Elena Borisovna; BORISOVA, Elena Nikolaevna; LYSIKOVA, Olga Valeryevna (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.v11.6(46).07, 2020)
The article is devoted to improving the technology of personnel training in the service sector. It is established that the cooperation of public associations and enterprises of various ownership forms with state and non-state educational institutions, as a principle of the system’s formation, has allowed for the introduction of a multi-level approach to the training of the service sector specialists with the simultaneous inclusion of additional education systems. Thus, the system of service education, combined with additional education, creates a fundamental position of education for service professionals. The authors have found that the features of the educational process in the service activities are regulatory support for the content of tourism education, a holistic approach to the content of education and training, consideration of the organic unity of general and professional education, strong links between theory and practice, and the partnership between the spheres of education and labour.